Examen especial a las cuentas de anticipos de fondos, inversiones en bienes de larga duración, ingresos y gastos de la asociación de gobiernos parroquiales rurales de la provincia de Los Ríos, periodo 2011-2012 - Drouet Murrieta, Adriana Isabel (2013)
The present research is the implementation of the evaluation to specific accounts of the Association of Rural Parish governments in the province of Los Rios through the Special Audit Review. As of this date on the association have not been executed audits or special examinations by any watchdog, reason to develop the research whose overall objective is to make the Special Consideration to the accounts of advances Funds, Investment Real Long Life, Income and Expenditure of Rural Parish Association of Governments in the province of Los Ríos in the period 2011-2012 . Specific goals that led us to fulfill the main objective as were raised : examine laws governing the institution, check for internal controls and regulations, verifying the legality and accuracy of processes accounts in the period under review . For the development of the field research work and documentation was used , and the analytical and deductive method , by which the information was collected , analyzed and verified the documents, and that the sources providing the information were primary and secondary . The methodological procedure of special consideration was the application of the three phases: 1. The preliminary and specific planning, 2. The conduct of the examination, and 3. The communication of results. Activities planned in the work programs were developed, internal control was assessed by use of internal control questionnaires, techniques and practices such as verbal verification audit, written, documentary and applied physics. The implementation of the research generated working papers and documents provided by the entity that ultimately entailed issuing the draft audit report with findings and recommendations to the audited entity.